Blood Glucose Levels and Performance in a Sports Camp for Adolescents with Type 1 Diabetes Mellitus: A Field Study. (23rd July 2010) - Kelly, Dylan; Hamilton, Jill K.; Riddell, Michael C.
Abstract : Background . Acute hypo- and hyperglycemia causes cognitive and psychomotor impairment in individuals with type 1 diabetes mellitus (T1DM) that may affect sports performance. Objective . To quantify the effect of concurrent and antecedent blood glucose concentrations on sports skills and cognitive performance in youth with T1DM attending a sports camp. Design/Methods . 28 youth (ages 6–17 years) attending a sports camp carried out multiple skill-based tests (tennis, basketball, or soccer skills) with glucose monitoring over 4 days. Glucose levels at the time of testing were categorized as (a) hypoglycemic (<3.6 mM); (b) within an acceptable glycemic range (3.6–13.9 mM); or (c) hyperglycemic (>13.9 mM). Results . Overall, sports performance skill was 20% lower when glucose concentrations were hypoglycemic compared to either acceptable or hyperglycemic at the time of skill testing (P < .05 ). During Stroop testing, "reading" and "color recognition" also degraded during hypoglycemia, while "interference" scores improved (P < .05 ). Nocturnal hypoglycemia was present in 66% of subjects, lasting an average of 84 minutes, but this did not affect sports skill performance the following day. Conclusions . Mild hypoglycemia markedly reduces sports skill performance and cognition in young athletes with T1DM.